INNOVATIVE METHODOLOGICAL APPROACHES TO FOREIGN LANGUAGE TEACHING WITHIN THE DUAL EDUCATION SYSTEM IN VOCATIONAL EDUCATION - Jabborberganova Hurriyat (TADQIQOTLAR, 2026)
Abstract: This essay investigates innovative methodological approaches for teaching foreign languages within the context of the dual education system in vocational education. It explores how dynamically merging theory and practice— central to dual education—necessitates new language pedagogy paradigms that connect classroom learning with real-world professional requirements. The discussion highlights integrative curricular strategies, technology-enhanced methodologies, student-centered learning environments, and multifaceted assessment practices as means to optimize language acquisition in vocational contexts. Drawing from recent research and practical experiences, particular emphasis is given to communicative competence, intercultural awareness, career-specific language needs, and the synergistic role of partnerships between educational institutions and industry. The conclusion summarizes the key findings and implications for educators and policymakers, while the reference list offers a foundation for further inquiry.